Intraosseous neurofibroma of maxilla in a child - Sharma P; Narwal A; Rana A; Kumar S (Wolters Kluwer Medknow Publications, 2009)
Central tumors of neurogenic origin are among the most rare primary jaw tumors in children. Intraosseous neurofibromas of the jaws occur more often as solitary lesions rather than as part of a generalized neurofibromatosis. We are presenting a case of solitary intraosseous neurofibroma of the maxilla in a five-month-old infant, which is probably the youngest such case published in literature so far.